Pengolahan Limbah Cair Sasirangan Menggunakan Filter Arang Aktif Cangkang Kelapa Sawit Berlapiskan Kitosan Setelah Koagulasi dengan FeSO4 - Utami Irawati; Umi Baroroh Lili Utami; Hanifa Muslima (Jurnal Sains dan Terapan Kimia, 2011)
Filtration of sasirangan wastewater using oil palm shell active charcoal coated with chitosan after coagulation with FeSO4 had been done. One of the aims of this research is to compare the value of pH, COD, Turbidity, TSS, total chromium and total lead in sasirangan wastewater after the treatment standards for waste quality set by Peraturan Gubernur Kalimantan Selatan Nomor 036 Tahun 2008, and to determine adsorption ability of filter based on the volume of Pb(II) solution being flown to 50 grams of adsorben. The wastewater of sasirangan was processed by using FeSO4 as coagulant under the optimum conditions at pH 8-10 and concentration 750 mg/l followed by filtration. Parameters of effluent being measured were pH, COD, Turbidity, TSS, total chromium and total lead. Determination of adsorption capacity of the filter  was done by flowing 35 liters of Pb(II) solution into the filter. The results showed that FeSO4 as coagulant has reduced pH value from 8,73-7,95 while the percentage of decrease for COD, TSS, turbidity and total lead were 93,33%, 56,95%, 65,10% and 10% respectively. After sasirangan wastewater was filtered, TSS, turbidity and total lead decreased as much as 77,25%, 87,63% and 77,78%. As much as 50 grams oil palm shell active charcoal coated with chitosan reach its saturation after being passed by 30 liters of Pb(II) solution.  Keywords: Sasirangan wastewater, coagulant FeSO4, active charcoal, chitosan